Engine emissions analysis of emulsified fuel of different blend ratios - Hazman, Abu Hassan; Hagos, F. Y.; Kadarohman, Asep; Sardjono, R. E.; Khoerunnisa, Fitri; Bo, Zhang; Jiang, X. X. (IOP Publishing, 2021)
Diesel engines are widely used because of their fuel efficiency in producing a higher mechanical energy ratio compared to gasoline engines. The current study is an extension of these efforts where diesel and biodiesel blend are modified to emulsify and oxygenate through water and alcohol to reduce NOx emissions from the exhaust. Biodiesel on the other hand, has the advantage of being sulfur-free, which reduces the emission of smoke and particulate matters but unfortunately increases NOx emissions. Meanwhile, emulsion fuel is found to lower the temperature of the cylinder during combustion and thus, reduce the release of NOx gas. The oxygenated fuels are tested for their emission behaviors in a four-stroke, single cylinder, water cooled, and direct fuel injection engine evaluated at a speed of 1200 rpm until 2400 rpm with the engine load varied at 0%, 50% and 100%. The method of fuel oxygenation and their effect on the concentration of NOx are discussed. The results have demonstrated a significant reduction in the NOx emission with an increase in the fraction ratio of palm oil biodiesel. The competition to produce high-performance and environmentally friendly fuels has made emulsion fuel and biodiesel renewable fuels believed to be new alternative fuels that emit very little NOx emissions into the atmosphere.